2022
DOI: 10.1038/s41586-022-04414-9
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism-based traps enable protease and hydrolase substrate discovery

Abstract: Hydrolase enzymes, including proteases, are encoded by 2–3% of the genes in the human genome and 14% of these enzymes are active drug targets1. However, the activities and substrate specificities of many proteases—especially those embedded in membranes—and other hydrolases remain unknown. Here we report a strategy for creating mechanism-based, light-activated protease and hydrolase substrate traps in complex mixtures and live mammalian cells. The traps capture substrates of hydrolases, which normally use a ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 65 publications
(90 reference statements)
0
39
0
Order By: Relevance
“…We identified two unreported Parkin substrates and validated their degradation by the ubiquitination-proteosome pathway. Very recently, a mechanism-based trap strategy was developed to discover hydrolase substrates by capturing the substrates with the enzyme 48 . While an extremely powerful approach, it is not suitable for profiling substrates involved in the formation of large complexes and requires the formation of a covalent bond between enzymes and substrates.…”
Section: Discussionmentioning
confidence: 99%
“…We identified two unreported Parkin substrates and validated their degradation by the ubiquitination-proteosome pathway. Very recently, a mechanism-based trap strategy was developed to discover hydrolase substrates by capturing the substrates with the enzyme 48 . While an extremely powerful approach, it is not suitable for profiling substrates involved in the formation of large complexes and requires the formation of a covalent bond between enzymes and substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 20 proteins that showed enrichment in the RHBDL4-FLAG fraction greater than 1.4-fold were the chaperones BiP and calreticulin; two protein disulfide isomerases, namely PDI and Erp44; and both subunits of the regulatory glucosidase II (Table S2). Recently, it has also been shown that these soluble ER chaperones are cleaved by RHBDL4, promoting their secretion (Tang et al, 2022); however, the physiological relevance of this finding remains to be addressed. Furthermore, two homologous membrane-integral ERAD factors, namely Er-lin1 and Erlin2, were enriched by 1.5-fold.…”
Section: Rhbdl4 Cleaves At a Defined Site But Additional Features Det...mentioning
confidence: 99%
“…This C-terminus contains the ER retention signal required for intracellular localization of CES2. In addition, RHBDL4 has been proposed as a hydrolase that liberates an array of ER-resident proteins into the extracellular space (Tang et al, 2022). Consistent with this idea, we were unable to detect peptides corresponding to C-terminus of either CES2A or CES2C ( Fig.…”
Section: Discussionmentioning
confidence: 99%